Maternal and fetal outcome in epidural analgesia study - Choudhary, Jaya; Sharma, Himanshu; Acharya, Veena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Labour is a highly complex event. Labour may be the most painful experience many women ever encounter. The objective of this study was to study the maternal and fetal outcome in epidural analgesia. Methods: A prospective study was conducted on 60 pregnant women. The study group (n = 60) consist of group A (epidural analgesia, n = 60) and group B (control, n = 30). Results: The maternal and fetal outcome in group A and group B were not statistically significant. Mean duration of first stage of labour (minute) was significantly lower in group A as compared to group B (p value <0.001). The duration of second stage of labour was prolonged in group A as compared to group B (p value 0.0137). The modes of delivery (normal, instrumental delivery, LSCS) were not statistically significant in both the groups. The neonatal outcome (Apgar score at 1 minute and 5 minutes) were statistically similar in both groups (P value = 0.569). Conclusions: Epidural analgesia is safe and effective to relieve the labour pain. It has no adverse maternal and fetal outcome. Patients are very comfortable and happy after epidural analgesia.